The Role of Secondary Metabolites Obtained from Medicinal and Aromatic Plants in Our Lives - Belgin Coşge Şenkal (ISPEC Journal of Agricultural Sciences)
Medicinal plants, which are used as drugs to prevent diseases, maintain health or cure diseases, take place in areas such as nutrition, cosmetics, body care, incense or religious ceremonies, while aromatic plants are used in different industrial areas to give fragrance and taste are used. Flora of Turkey has a rich plant diversity. Secondary metabolites such as essential oils, alkaloids, glycosides, saponins etc. are the most basic products of the industry directly or indirectly. The vast majority of medicinal and aromatic plants rich in secondary metabolites exhibit strong biological activity (antioxidant, antibacterial, etc.). Therefore, these secondary metabolites are widely used in the pharmaceutical industry. The most common and practical use of secondary metabolites, which are also used as natural insecticides, is in the form of herbal tea. In recent years, the more side effects of synthetic origin substances, especially the resistance of organisms against synthetic drugs used as antimicrobials, have increased the importance of natural herbal resources and medicinal plants carrying these substances. Therefore, there is no doubt that the demand for secondary metabolites, which are natural products, will increase in the future. Flora of Turkey is an important source for natural products which will be developed newly.